2023
DOI: 10.1007/s12469-023-00322-x
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in scheduling and execution of trackwork in Sweden

Daria Ivina,
Nils O. E. Olsson,
Carl-William Palmqvist
et al.

Abstract: Trackwork planning and scheduling are demanding because they require strategic foresight and must be completed well in advance. In Sweden, trackwork is performed by maintenance contracting companies during an operation period free from trains. In the contractors’ practice, once the maintenance plan is authorised, some unexpected events might interrupt the plan’s execution, leading to uncertainties. The purpose of this study is to identify and classify uncertainties and strategies applied to manage uncertaintie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…The stability of the trackwork schedule diminishes as the execution date approaches. This observation aligns with [17,19], highlighting the impact of uncertainties on trackwork project performance, often resulting in frequent rescheduling, and requiring train timetable adjustments. One possible explanation for this issue might be the absence of incentives imposed by the Swedish Transport Administration on contractors to adhere to the schedule as the execution date draws near.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…The stability of the trackwork schedule diminishes as the execution date approaches. This observation aligns with [17,19], highlighting the impact of uncertainties on trackwork project performance, often resulting in frequent rescheduling, and requiring train timetable adjustments. One possible explanation for this issue might be the absence of incentives imposed by the Swedish Transport Administration on contractors to adhere to the schedule as the execution date draws near.…”
Section: Discussionsupporting
confidence: 75%
“…According to [17], it is relatively common to reschedule trackwork in response to disruptions or unexpected events. Unexpected events and disruptions that can affect trackwork scheduling include equipment unavailability, staff shortages, changes in work priorities, and changes in work order.…”
Section: Trackwork Reschedulingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it has been observed that this approach is not yet utilised to its full potential, and train operators may have difficulty adapting to the restrictions. Additionally, there may be uncertainty [37] in the trackwork schedule even close to the execution period, which can lead to changes in the schedule and difficulties for train operators to adapt, resulting in train cancellations.…”
Section: Discussionmentioning
confidence: 99%